Population-based study on the prevalence and clinical profile of adults with cerebral palsy in Northern Ireland. Issue 1 (8th January 2021) - McConnell, Karen; Livingstone, Emma; Perra, Oliver; Kerr, C
Abstract : Objectives: This study aimed to report the prevalence and clinical characteristics of adults with cerebral palsy (CP) in a geographically defined region of the UK. Design and setting: Cross-sectional study using the Northern Ireland Cerebral Palsy Register (NICPR). Participants: All validated cases known to the NICPR, born 1981–2001 and alive and resident in Northern Ireland at age 19 years were included. Results: The study included 1218 persons with CP aged 19–39 years, 46 of whom died in adulthood. The prevalence of CP was 2.38 per 1000. The majority of cases had spastic CP (n=1132/1218, 93%) and could walk (n=949/1218, 78%). Those that died in adulthood typically had bilateral spastic CP (n=39/46) and used a wheelchair (n=40/46). Conclusion: The prevalence of CP in adults is similar to other common neurological conditions such as multiple sclerosis and Parkinson's disease. The needs of adults with CP vary widely with almost half having two or more associated impairments that may require multiprofessional and multiagency coordination. Results from this study can be used to inform transformation of health and care services for adults with CP.